If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 3) = 8a Reorder the terms: 3(3 + x) = 8a (3 * 3 + x * 3) = 8a (9 + 3x) = 8a Solving 9 + 3x = 8a Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 3x = -9 + 8a Combine like terms: 9 + -9 = 0 0 + 3x = -9 + 8a 3x = -9 + 8a Divide each side by '3'. x = -3 + 2.666666667a Simplifying x = -3 + 2.666666667a
| 2(xa-3)=x-a | | x+2+8=6x | | 2(ax-3)=x-a | | 6=-8-2x | | x^2+3xy=10 | | 7(a+5)-11=3(a+2) | | 2(5d+13)-14=8 | | (6a+1)(a+1)=21 | | 9-18x-12=10x+10-25x | | 12a^2-13ab-4b^2= | | r=6 | | 5a+7a= | | 4p^2-17pq-4p^2= | | 3az+2bw+3aw+2bz= | | 2*(5X-8)-3(4X-5)=4(3X-4)+11 | | 15-7x-2x^2= | | 6b+4=2(2b-1) | | 8x^2+22xy-21y^2= | | 116=-4(1+6a) | | 4x^2-15xy+9y^2= | | t^2+6t-3=0 | | 3(9-8)= | | -7(3k-3)=-84 | | t^2+t-30= | | -(2n+6)=-(n-1)-n | | -(-4-5x)=-8(7+2x)+x | | Z^2-22-15= | | 5y+2y-y+3w= | | 4x+14=74-6x | | t^2-12t-45= | | 5(8k+8)= | | 5(x-2)=-45 |